Kepadatan Populasi Kepiting Bakau (Scylla Serrata Forskal) Pada Kawasan Hutan Mangrove Di Teluk Buo Kecamatan Bungus Teluk Kabung Padang Sumatera Barat - Yuniati, Reni; Nurhadi, Nurhadi; Lusi, Armein (Pendidikan Biologi, 2013)
ABSTRACT         Mangrove crab (Scylla serrata Forskal) is one of commodity that many liked the beach because the meat tastes delicious, especially the crab meat that are laying and high protein content. Gulf Buo area there is a lot of mud crab especially S. serrata Forskal, but with the continuous arrests (Overfishing) conducted by the society mud crab population has declined. This research aims to determine the density of mangrove crabs and physical factors in the Gulf Buo water chemistry Bungus sackcloth Bay District Padang West Sumatra. Types of the research that used is descriptive that take the sampling directly in the field by using transects that placed by purposive sampling is choosing a location based on the selected mangrove vegetation then chooses 3 stations. The results of research that has been conducted found 44 individuals, the highest density at station II is 2.1 individuals/traps, the average density of 1.47 individuals/trap. The physical factors water chemistry still in accordance with the range of tolerance for the life of the mangrove crab with 24-30 ppt salinity, temperature from 29.0 to 30.7 0C, pH at the third station 7, and 4.90 to 6.26 ppm DO. This research can conclude that the population density of Mangrove Crab Scylla serrata Forskal on Mangrove Forests in the Gulf Buo Bungus sackcloth Bay district of West Sumatra Padang as much as 1.47 individuals/trap. Water chemistry physics factor is still within the range that is good enough to support life mud crab.